Gradient lithiophilic metal foam via magnetic sputtering deposition in dendrite free lithium metal anodes - Liu, Wenlong; Man, Jianzong; Sun, Xiaodong; Zhang, Ning; Zhang, Haibang; Liu, Kun; Wen, Zhongsheng; Li, Song; Sun, Juncai (Chemical engineering journal (Lausanne, Switzerland : 1996), 2025)
The development of lithium (Li) metal anodes (LMAs) has garnered widespread attention owing to their unparalleled advantages, including high theoretical specific capacity and energy density. However, the growth of dendrites and volume change present significant obstacles, thereby impeding the progress of LMAs. In this study, lithiophilic tin (Sn) layers were successfully deposited on one side of copper (Cu) foam via magnetron sputtering. Owing to the short transportation distance and the absence of a significant driving force, the deposited Li tends to accumulate at the top of the Cu foam. Density functional theory calculations reveal that the Sn layer possesses a greater adsorption energy with respect to Li+ than Cu does. Consequently, the Sn layer is effective in attracting free Li+ and guiding their movement in the vertical orientation. Besides, the current density distribution on the electrode surface has been simulated by COMSOL software. Obviously, the presence of lithium affinity gradient can effectively increase the current density and ion concentration at the bottom of the electrode and promote the deposition mode from bottom to top. Benefiting from the porous structure and the gradient lithiophilicity, the modified sample exhibits high cycle capacity and long cycle life. The difference between the bottom (Sn) and top (Cu) section could attract the Li+ to deposit form the bottom and gradually fill in the whole foam structure, suppressing the top deposition caused by the short transmission paths. [Display omitted] •A lithiophilic Sn layer is prepared on one side of Cu foam by magnetron sputtering.•The gradient lithiophilicity structure promotes the deposition from bottom to up.•The distribution of current density and ion concentration could be optimized by gradient structure.•Benefiting from gradient structure, the interspace of foam could be fully utilized.•The symmetric cells can stable run more than 2200 h at 1 mA cm−2 with 1 mAh cm−2.